Às coisas mesmas: contribuições fenomenológico-hermenêuticas à clínica psicológica fundamental - Fonseca, Felipe Suster Gomes (2016)
To seek the phenomenological hermeneutic experience and interpret the conditions of clinical psychology in its own phenomenal happening; this is the core of this work. To proceed with this claim, we will take the phenomenological and hermeneutical philosophy trying to occupy their own places. Heidegger is the greatest exponent of this way of thinking, that's why we will reserve more attention to the thinker from the Black Forest, as he could contribute to the pursuit of our fundamental experience, but always in conjunction with two important influences (Dilthey and Husserl). Thus, we can’t equivocate on to characterize this work as a heideggerian proposal. We'll present essays that tried to penetrate the nerve of thinking that is inculcated in the fundamental experience of his own phenomenology- hermeneutics, reducing spaces interpreting own corresponding authors of this philosophical school. For this, we will not focus on a conceptual appropriation in view of applicability of such a philosophy. Our contribution to the psychological clinic will take place in the thinking of the sense of being of our theoretical life in his historical happening, keeping the manifest phenomenological field as interpretative possibility of our horizon of meaning